2007
DOI: 10.1097/wnr.0b013e3281667d59
|View full text |Cite
|
Sign up to set email alerts
|

Event-related potential N270 correlates of brand extension

Abstract: The aim of this study is to investigate the neural mechanism of extending a brand in a specific product category to other product categories. Facing two sequential stimuli in pairs consisting of beverage brand names (stimulus 1) and product names (stimulus 2) in other categories, 16 participants were asked to indicate the suitability of extending the brand in stimulus 1 to the product category in stimulus 2. These stimulus pairs were divided into four conditions depending on the product category in stimulus 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
75
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 23 publications
3
75
4
1
Order By: Relevance
“…This result is different from Ma et al's previous study about brand extension, in which Ma et al employed a S1-S2 paradigm to examine the brand extension (Ma et al, 2007). In that prime-probe designed experiment, priming of stimulus 1 (S1) and probing of stimulus 2 (S2) were presented sequentially, and only a negative component, N270, in 200-300 ms in the fronto-central region was found, but no significant negative component was observed in the occipito-temporal area.…”
contrasting
confidence: 82%
See 3 more Smart Citations
“…This result is different from Ma et al's previous study about brand extension, in which Ma et al employed a S1-S2 paradigm to examine the brand extension (Ma et al, 2007). In that prime-probe designed experiment, priming of stimulus 1 (S1) and probing of stimulus 2 (S2) were presented sequentially, and only a negative component, N270, in 200-300 ms in the fronto-central region was found, but no significant negative component was observed in the occipito-temporal area.…”
contrasting
confidence: 82%
“…The stimulus paradigm used in the current study is closer to what consumers face in the marketplace than the S1-S2 paradigm used by Ma et al (2007Ma et al ( , 2008Ma et al ( , 2010. It is the first time that evidence has been found that enables speculation regarding a dual conflict in the cognitive process in the experiment with the W1W2 paradigm.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Moreover, previous studies also used event-related potentials (ERPs) to investigate the evaluation of brand extension. For example, Ma et al [8] first used ERPs to study brand extension, in which they found a negative component N270, the amplitude of which varied according to the conflict between the brand name and the product category.…”
Section: Introductionmentioning
confidence: 98%